Adaptation and validation of two screening instruments of mental health of first grade schoolchildren of Santiago - George, Myriam; Siraqyan, Ximena; Morales, Randa; Barra De La, Flora; Rodríguez, Jorge; López, Carmen; Toledo, Virginia (Revista de Psicología, 1994)
The adaptationand validation of two questionnaires -teacher and parents rating scales- that asses maladaptative behaviors in 1st grade children is described. A sample of 595 children attending seven schools of Santiago was used. The statistical analysis showed acceptable levels of internal consistency for both instruments and a factorial structure for the teacher’s scale discriminating different behavioral areas. Finaly standarized norms, separately for males females, were obtained.